Site quality equations for Abies religiosa in different regions of Mexico - Guzmán-Santiago, Juan Carlos; Aguirre-Calderón, Oscar Alberto; Vargas-Larreta, Benedicto; Gómez-Cárdenas, Martín; De los Santos-Posadas, Héctor Manuel; Quiñonez-Barraza, Gerónimo; Marroquín-Morales, Pablo (Instituto de Ecología, A.C., 2021)
The estimates of dominant height or site index allow evaluating the productivity of forest stand and function as tool within the forest management plan for harvesting purposes. This work aimed to analyze dynamic site index curves with the generalized algebraic difference approach (GADA) in 12 Forest Management Units for Abies religiosa in different regions of Mexico. 262 stem analysis samples from dominant and codominant trees were used, which were fitted with the Richards model using the GADA by ordinary least squares. With this approach, the parameters of growth rates and asymptotes can be expanded, allowing more than one parameter of the model to depend on the quality of the site, making polymorphic curves with multiple asymptotes more flexible. Autocorrelation was also corrected using the Durbin Watson (DW) statistical test. In general, significant gains were obtained for all sites, obtaining errors of less than 1.2 m and adjusted coefficients of determination that explain more than 97% of the total variance of growth in height as a function of age, as the DW values approximate to 2 in which it rectifies the values provided by Akaike information criteria, which is desirable for modeling growth trend data without affecting site index predictions. The equations are recommended to develop management plans for this species at different sites to classify timber productivity.